An in vitro investigation into the effects of postbiotic supplementation on stabilising equine hindgut pH - L. Sheridan; P. Hutton; G. Noble; B. Nobari (Journal of Equine Veterinary Science, 2026)

Prevalence of key resistance alleles associated with DMI and SDHI fungicide resistance in European Zymoseptoria tritici populations in 2022 - S. Kildea; T. Heick; F. Hutton; C. Bataille; L. Aldén; J. Kaneps; A. Mäe; S. Weigand; J. Zajc; A. S. Walker; P. Hellin (Journal of Plant Diseases and Protection, 2025)

Characterization of sites of scientific interest for ESA's PROSPECT instrument - S.J. Boazman; D. Heather; M. Hutton; M. Schwinning; A. Frigeri; N. Schmitz; S. Besse; M. Formisano; C. De Sanctis; C. Gscheidle; C. Orgel; P. Reiss; et al. (Icarus, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Food and temperature stressors have opposing effects in determining flexible migration decisions in brown trout ( Salmo trutta ) - Louise C. Archer; Stephen A. Hutton; Luke Harman; Stephen D. McCormick; Michael N. O’Grady; Joseph P. Kerry; W. Russell Poole; Patrick Gargan; Philip McGinnity; Thomas E. Reed (Global Change Biology, 2020)
With rapid global change, organisms in natural systems are exposed to a multitude of stressors that likely co‐occur, with uncertain impacts. We explored individual and cumulative effects of co‐occurring environmental stressors on the striking, yet poorly understood, phenomenon of facultative migration. We reared offspring of a brown trout population that naturally demonstrates facultative anadromy (sea migration), under different environmental stressor treatments and measured life history responses in terms of migratory tactics and freshwater maturation rates. Juvenile fish were exposed to reduced food availability, temperatures elevated to 1.8°C above natural conditions or both treatments in combination over 18 months of experimental tank rearing. When considered in isolation, reduced food had negative effects on the size, mass and condition of fish across the experiment. We detected variable effects of warm temperatures (negative effects on size and mass, but positive effect on lipids). When combined with food restriction, temperature effects on these traits were less pronounced, implying antagonistic stressor effects on morphological traits. Stressors combined additively, but had opposing effects on life history tactics: migration increased and maturation rates decreased under low food conditions, whereas the opposite occurred in the warm temperature treatment. Not all fish had expressed maturation or migration tactics by the end of the study, and the frequency of these ‘unassigned’ fish was higher in food deprivation treatments, but lower in warm treatments. Fish showing migration tactics were smaller and in poorer condition than fish showing maturation tactics, but were similar in size to unassigned fish. We further detected effects of food restriction on hypo‐osmoregulatory function of migrants that may influence the fitness benefits of the migratory tactic at sea. We also highlight that responses to multiple stressors may vary depending on the response considered. Collectively, our results indicate contrasting effects of environmental stressors on life history trajectories in a facultatively migratory species.

Genetic divergence between colonies of Flesh-footed Shearwater Ardenna carneipes exhibiting different foraging strategies - Anicee J. Lombal; Theodore J. Wenner; Jennifer L. Lavers; Jeremy J. Austin; Eric J. Woehler; Ian Hutton; Christopher P. Burridge (Conservation Genetics, 2018)

Effects of parental care on the accumulation and release of cryptic genetic variation: review of mechanisms and a case study of dung beetles - Emilie C. Snell-Rood; Melissa Burger; Quinton Hutton; Armin P. Moczek (Evolutionary Ecology, 2016)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

What relative seafood prices can tell us about the status of stocks - John K Pinnegar; Trevor P Hutton; Vincenzo Placenti (Fish and Fisheries, 2006)
Changes in the distribution of seafood prices can provide useful insights into the availability of different species to fishermen and to fish markets. We propose a log‐relative‐price‐index (LRPI) and demonstrate how such a concept might be useful for exploring long‐term changes in wild fish communities as a result of intensive exploitation. We estimate the LRPI for 26 fish species in the Celtic Sea (UK) and for 33 species on Italian fish markets. In both systems the LRPI changed significantly during recent decades, and in the Celtic Sea this probably resulted from a decline in the availability of high trophic level target species such as cod and hake as well as an increase in the availability of low trophic level pelagic species. By contrast, the LRPI of Italian fishes remained relatively constant from 1972 to 1980, but declined thereafter as a result of widespread expansion in fin‐fish aquaculture, and a consequential increase in the supply, and hence decrease in the price of high trophic level fish such as seabass and seabream.

Field resistance of annual pasture legumes to the root lesion nematode, Pratylenchus neglectus - R. A. Ballard; R. E. Hutton; S. P. Taylor; A. C. McKay; J. H. Howie (Australasian Plant Pathology, 2006)

Tryptophan?NAD+ pathway metabolites as putative biomarkers and predictors of peroxisome proliferation - Jane Delaney; Mark P. Hodson; Hansa Thakkar; Susan C. Connor; Brian C. Sweatman; Steve P. Kenny; Paul J. McGill; Julie C. Holder; Kathryn A. Hutton; John N. Haselden; Catherine J. Waterfield (Archives of Toxicology, 2005)

Failure of Marine Deposits and their Redistribution by Sediment Gravity Flows - J. P. M. Syvitski; E. W. H. Hutton (Pure and Applied Geophysics, 2003)

Turbulence Statistics Measurements in a Northern Hardwood Forest - M. G. Villani; H. P. Schmid; H.-B. Su; J. L. Hutton; C. S. Vogel (Boundary-Layer Meteorology, 2003)

Laboratory Kinetic Studies of the Reactions of Cl Atoms with Species of Biogenic Origin: δ3-Carene, Isoprene, Methacrolein and Methyl Vinyl Ketone - Carlos E. Canosa-Mas; Hilary R. Hutton-Squire; Martin D. King; David J. Stewart; Katherine C. Thompson; Richard P. Wayne (Journal of Atmospheric Chemistry, 1999)

Heterogeneity in the protein cores of mucins isolated from human middle ear effusions: evidence for expression of different mucin gene products - David A Hutton; Fiona J.J Fogg; Haytham Kubba; John P Birchall; Jeffrey P Pearson (Glycoconjugate Journal, 1998)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)